Local indicators for global species: Pelagic sharks in the tropical northeast Atlantic, Cabo Verde islands region. (March 2020) - Coelho, Rui; Macías, David; Ortiz de Urbina, Josetxu; Martins, Albertino; Monteiro, Carlos; Lino, Pedro G.; Rosa, Daniela; Santos, Catarina C.; Bach, Pascal; Murua, Hilario; Abaunza, Pablo; Santos, Miguel N.
Highlights: Pelagic sharks are an important component of oceanic fisheries. Stock status indicators for two of the main shark species were developed. Satellite telemetry was used to model the spatial distribution of the species. One indicator for one species raises concern in terms of possible overfishing. Locations of concentration of juveniles should be prioritized for conservation. Abstract: Pelagic sharks are an important bycatch in pelagic fisheries, especially for drifting longlines targeting swordfish. In the Cabo Verde Archipelago (tropical NE Atlantic), pelagic shark catches can reach a significant proportion of the total catches. Due to the increased concern on the status of pelagic shark species, this study was developed to enhance the current knowledge of those sharks in the Cabo Verde region in comparison to the adjacent areas, especially associated with European Union (EU) pelagic longline fishing activity. Stock status indicators for the two main species, blue shark ( Prionace glauca) and shortfin mako ( Isurus oxyrinchus ), were developed, based on fisheries data from logbooks and onboard scientific observers, including analysis of size frequency distributions and standardized catch-per-unit-of-effort (CPUE) indexes over time. The standardized CPUEs have been stable or increasing for both species in the past 10 years, indicating no signs of local depletion. In terms of sizes, the blue shark catch is composed mainly of adults, which can be a sign of a stable population. On the contrary, the catch of shortfin mako is composed mainly of juveniles, which in conjunction of a decrease of mean size might be a cause of concern, highlighting possible overfishing on the species in the region. Thirty satellite tags, 25 archival miniPATs and 5 SPOT GPS, were deployed in the Cabo Verde Exclusive Economic Zone (EEZ), showing that those species are highly mobile. The biomass and size distributions were modeled with spatial and seasonal models (GAMs) identifying locations where juveniles are predominantly concentrated and that should be prioritized for conservation. This work presents new information on the status of pelagic sharks in the Cabo Verde region in the context of those highly migratory species, and can now be used to promote more sustainable fisheries in the region.